Return Of The Home Run Kid - Christopher, Matt; Casale, Paul (New York Scholastic, 1992)
Last year, sylvester was the '' kid who only hit homers,'' but this season it seems like he can't do anything right, he's playing so badly that the coach has him warming the bench-until he meets cheeko, with cheeko's help, sylvester learns how to play tough, suddenly he's hot again, but why don't his friends like syl's new style? why do they say he's heading for trouble? and what is cheeko hiding?
American Corner
11
Keywords: English Fiction; English Stories